Masa Depan Ekonomi Islam di Indonesia: Analisis Peluang, Tantangan, dan Strategi - Parembai, Murni (Tijarah: Jurnal Ekonomi Syariah, 2024)
Indonesia as the country with the largest Muslim population has strategic potential in the development of regional and global Islamic economics. This study aims to analyze the growth of the Islamic economy in Indonesia, the challenges faced, and strategies to strengthen it. The method used is a literature study with a qualitative descriptive approach to government policies, the development of the halal industry, and Islamic finance. The results showed that the growth of the Islamic economy in Indonesia is increasing rapidly, but the challenges of low Islamic financial literacy, limited human resources, and institutional infrastructure are still an obstacle. Synergy between the government, industry, and society is needed to encourage Islamic financial inclusion and strengthen national halal products.ABSTRAKIndonesia sebagai negara berpenduduk Muslim terbesar memiliki potensi strategis dalam pengembangan ekonomi Islam regional dan global. Penelitian ini bertujuan menganalisis pertumbuhan ekonomi Islam di Indonesia, tantangan yang dihadapi, serta strategi penguatannya. Metode yang digunakan adalah studi literatur dengan pendekatan deskriptif kualitatif terhadap kebijakan pemerintah, perkembangan industri halal, dan keuangan syariah. Hasil penelitian menunjukkan pertumbuhan ekonomi Islam di Indonesia meningkat pesat, namun tantangan rendahnya literasi keuangan syariah, keterbatasan SDM, dan infrastruktur lembaga masih menjadi hambatan. Diperlukan sinergi antara pemerintah, industri, dan masyarakat untuk mendorong inklusi keuangan syariah dan penguatan produk halal Nasional.